A midiatização das patentes sob o olhar CTS (Ciência, Tecnologia e Sociedade) - Mazocco, Fabricio José (2009)
This paper intends to study patents as a media information source. This research identified the characteristics of this techno-scientific product that somehow calls press media s attention; also, it aims to set discussions on the relation between media and patents from STS studies (Science, Technology and Society). It took as empirical object the newspapers Gazeta Mercantil (GM) and Valor Econômico (VE). All news about patents, involving aspects such as legal issues involving patents protection, patents seen as an innovation sign, patent as an instrument for Science and Technology (S&T) construction, patents system, technical details about patents, and others. This paper starts in a presumption: mass media still approach patents in an economical way and follows offer-line model logics in this way, basic research is followed by applied research and later by technological development that allows new products and society benefits. Methodology of content analysis was used on news about patents. It was verified that patents, a product of techno-science, has elements to make it a precious source of information to mass media. When dealing with the necessary requirements in order to patent any innovation, foreseen in law, we stand out the importance to divulge it, in order to spread not only technical issues but also social elements.